Comparative analysis of antimicrobial drugs recommended by medical and technological documents for the treatment of patients with community-acquired pneumonia - L. V. Iakovlieva; T. O. Bahlai; O. V. Khomenko (The State Expert Center of the Ministry of Health of Ukraine, 2019)
Today community-acquired pneumonia remains one of the leading causes of death as a result of infectious diseases. For effective treatment must be guided by such guidelines which would take into account not only recent world experience in the field of antimicrobial therapy but also regional peculiarities of the microbial spectrum and the resistance to pathogens of this nosology. The aim of the work was to conduct a comparative analysis of antimicrobial drugs recommended for the treatment for patients with community-acquired pneumonia. The assortment of major antimicrobial drugs was studied according to the «Pharmstandard» system of the «Morion» company. Also, the research used data of medical and technological documentation of Ukraine, Great Britain, USA. Current the Unified Protocol for the provision of medical care to adult patients with community-acquired pneumonia and the State Medicines Directive offer almost identical antimicrobial drugs and differ only in those that do not have a proof-based basis. Leading international sources recommend a smaller number of drugs whose trade names are sufficient in the domestic market, and pharmacological properties suggest a rational pharmacotherapy of patients with community-acquired pneumonia when using them. Medical and technological documents offer for pharmacotherapy of patients with community-acquired pneumonia more than 20 preparations with more than 500 product names mainly present on the domestic market; in foreign directions a number of drugs (cefaclor, flucloxacillin, temocylin, piperacillin, colistin) are recommended, which are not in the domestic documentation, whose pharmacological properties and price range are rational to have for treatment of patients with community-acquired pneumonia.